Nickel‐Iron Alloy Nanoparticle‐Decorated K2NiF4‐Type Oxide as an Efficient and Sulfur‐Tolerant Anode for Solid Oxide Fuel Cells. Issue 9 (8th June 2017) - Wu, Nuo; Wang, Wei; Zhong, Yijun; Yang, Guangming; Qu, Jifa; Shao, Zongping
Abstract: We report a new nickel‐iron alloy nanoparticle‐decorated LaSrFe0.75 Ni0.25 O4 K2 NiF4 ‐type oxide with Ruddlesden‐Popper structure (RP‐LSFN), which performed as a high‐performance sulfur‐resistant anode prepared by using an infiltration method for solid oxide fuel cells (SOFCs) with LaSrFeNiO6‐δ double perovskite (DP‐LSFN) as the precursor. A reduction converts the DP‐LSFN phase into mixed phases containing the RP‐LSFN and FeNi3 nanoparticles. The morphology, thermal expansion behavior, sulfur tolerance, and electrochemical activity for hydrogen oxidation of this FeNi3 nanoparticle‐decorated, RP‐LSFN‐infiltrated anode are investigated. An electrolyte‐supported SOFC with this infiltrated anode generates a high power output of 541 mW cm −2 at 800 °C operated with 1000 ppm H2 S−H2 as the fuel, which compares favorably to that with pure H2 fuel. A single cell with this anode demonstrates favorable stability at 800 °C during 90, 40, and 20 h operation with H2 containing 100, 200, and 1000 ppm H2 S, respectively. Abstract : Get the decorators in : A new nickel‐iron alloy nanoparticle‐decorated LaSrFe0.75 Ni0.25 O4 K2 NiF4 ‐type oxide with Ruddlesden‐Popper structure is used as a high‐performance sulfur‐resistant anode for solid oxide fuel cells. With LaSrFeNiO6‐δ double perovskite, prepared through the infiltration method, as the precursor, this highly active infiltrated anode displays excellent sulfur tolerance and good stability.